Las formas del mundo en el México antiguo - Díaz, Ana (Studi e materiali di storia delle religioni, 2020)
Among the themes that arouse great interest in addressing the study of ancient cultures, the conception of the cosmos plays a special role. Early New Hispanic manuscripts present the first attempts at exploration in this field, offering first-hand information to reconstruct the cosmography of Pre-Columbian Mexicans. This article offers a detailed study of four documents that refer different versions of the composition of the universe among the Nahuas. I try to demonstrate that the data offered in these sources do not reflect the vision of the pre-Hispanic Nahua world, but that they creatively and effectively integrate elements of indigenous tradition reconfigured under the paradigms of the Christian cosmography of the moment. This organization contrasts with the vision of the Nahua world, where each group had to build their own cosmological discourse, taking into account their history, their genealogy and the political relationships that shaped their complex social framework.